Psychosocial factors in self-destructive behaviors in adolescents - Junco Supa, Jenny Elsa (2002)
This article analyses psychosocial factors affecting adolescents’ suicidal behavior by highlighting family relationship level within an interactive relationship. At the same time, the article tries to focus this reality as a public health problem